Alternatif Kebijakan Public Service Reform dalam Meningkatkan Kualitas Pelayanan Publik - Joni Dawud (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2004)
The improvement of public service quality has turned out to be the main objectives in the public sector reform. The policy target is to promote the non-government sectors, namely, the private sector and society to increase its participation inÂ  providing public service. In addition, the internal policy needs to be reformulated, concerning both the system and the personnel implementing the system.Â